Knowledge and Awareness of CT Radiation Dose and Risk Among Patients. (September 2018) - Al Ewaidat, Haytham; Zheng, Xiaoming; Khader, Yousef; Spuur, Kelly; Abdelrahman, Mostafa; Alhasan, Mostafa Khaled Mustafa; Al-Hourani, Zeid A.
The study aims to assess the level of patients' awareness and knowledge regarding radiation and dosage along with the associated risks from computed tomography (CT) scan. This cross-sectional study used questionnaires, which were distributed to the diagnostic imaging departments of six large local hospitals in Jordan between September 2014 and March 2015. A total of 600 patients completed the questionnaire, out of which, 52.33% of respondents were female and 47.6% male. The findings show insignificant effects of gender on patient's knowledge ( P = .596) and significant effect of employment and profession on positive scores ( P = .000). Similarly, no statistical differences were found between gender and correct answers ( P = .707). This cohort of patients demonstrated a lack of awareness and knowledge about the use of ionizing radiation for diagnostic imaging. Thus, there may exist a similar lack of information that will require imaging professionals to raise patients' awareness and offer them the appropriate information.